2004
DOI: 10.1111/j.1365-2222.2004.01979.x
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic acid in perilla extract inhibits allergic inflammation induced by mite allergen, in a mouse model

Abstract: These results suggest that oral administration of perilla-derived rosmarinic acid is an effective intervention for allergic asthma, possibly through the amelioration of increases in cytokines, chemokines, and allergen-specific antibody.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(93 citation statements)
references
References 51 publications
1
83
0
5
Order By: Relevance
“…Previous investigations have discovered that some polyphenols extracted from P. frutescens exhibit pharmacological activities such as anti-allergy, anti-inflammatory [1] and anti-oxidant [2]. Among these components, luteolin and apigenin, the common flavones which are contained in a wide range of beneficial or dietary plants including weld (Reseda luteola L.), carrot (Daucus carota subsp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigations have discovered that some polyphenols extracted from P. frutescens exhibit pharmacological activities such as anti-allergy, anti-inflammatory [1] and anti-oxidant [2]. Among these components, luteolin and apigenin, the common flavones which are contained in a wide range of beneficial or dietary plants including weld (Reseda luteola L.), carrot (Daucus carota subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Generally substances were prepared with organic solvents such as ethanol, methanol, acetone and toluene. Whereas some researchers developed and applied sophisticated methods [2], simple maceration at a range of temperatures is broadly accepted and common practice [1,3]. Recently, supercritical carbon dioxide (SC-CO 2 ) extraction has provoked considerable interest as a separation technique in many fields [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Several in vivo and in vitro studies have demonstrated that perilla can suppress IgE-mediated responses, [1][2][3] and no previous cases of allergic reactions or anaphylaxis induced by the perilla seed have been reported.…”
Section: Two Cases Of Anaphylaxis Caused By Perilla Seedmentioning
confidence: 99%
“…However, allergists in Australia, 2 Britain, 3 and France, 4 among others, often rely on skin prick testing (SPT) in the diagnosis of food allergy. We would therefore like to share our experience in defining cutoff values for SPT wheal diameters that predict positive challenge outcomes to tree nuts and sesame.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation